SEMANTIC FUNCTIONS OF SPEECH SOUNDS AND PHONEME ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the fundamental roles of speech sounds and phonemes in human communication, focusing on their semantic functions and linguistic significance. Speech sounds, the physical articulations of language, and phonemes, the abstract units of sound, form the core of how spoken language conveys meaning. The article highlights the distinction between the two, emphasizing their interplay in differentiating words, signaling grammatical relationships, and expressing emotions or emphasis. Key points include the differentiation of lexical items through phonemic contrast, the role of phonological rules in shaping pronunciation, and cross-linguistic variations such as tonal versus non-tonal systems. Additionally, the article delves into the cognitive and social dimensions of speech sounds, illustrating their importance in language processing and identity formation. This analysis provides a comprehensive overview of how sound patterns in language serve as a bridge between articulation and meaning, offering insights into the intricate structure and function of human language.